1985
DOI: 10.1128/aac.28.6.781
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of amikacin and ceftazidime in experimental aortic valve endocarditis due to Pseudomonas aeruginosa

Abstract: The in vivo efficacies of amikacin, ceftazidime, and their combination were evaluated in experimental aortic valve endocarditis due to Pseudomonas aeruginosa. Eighty catheterized rabbits were infected with a P. aeruginosa strain susceptible to both amikacin and ceftazidime and then received no therapy (controls), amikacin (15 mg/kg per day), ceftazidime (100 mg/kg per day), or amikacin-ceftazidime. Amikacin Morrison, Chemotherapy [Basel], in press). In that study, the amikacin-ceftazidime regimen was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
43
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 21 publications
(25 reference statements)
3
43
1
Order By: Relevance
“…Recent experiences in our laboratory and others have demonstrated that in vivo development of P-lactam resistance is an important determinant of therapeutic efficacy in treating invasive pseudomonal infections (1,16,19,22,23). This problem has remained prevalent despite the development of cephalosporins with potent antipseudomonal activity in vitro and which are relatively resistant to P-lactamase hydrolysis (e.g., ceftazidime, cefoperazone).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent experiences in our laboratory and others have demonstrated that in vivo development of P-lactam resistance is an important determinant of therapeutic efficacy in treating invasive pseudomonal infections (1,16,19,22,23). This problem has remained prevalent despite the development of cephalosporins with potent antipseudomonal activity in vitro and which are relatively resistant to P-lactamase hydrolysis (e.g., ceftazidime, cefoperazone).…”
Section: Discussionmentioning
confidence: 99%
“…One of the limiting factors in this regard, as exemplified in human as well as experimental Pseudomonas endocarditis, has been in vivo development of antibiotic resistahce. Such resistances have been variably directed towards the aminoglycoside or P-lactam components of the combination therapy regimens generally used to treat Pseudomonas endocarditis (1,19,23,26). The mechanism of P-lactam resistance in these situations has usually been associated with either inducible or constitutive P-lactamase overproduction (3,19,26).…”
mentioning
confidence: 99%
See 3 more Smart Citations